State Fragility and Sustainable Development Goals in Egypt - Elmakkawe, Mahmoud (AUC Knowledge Fountain, 2021)
This study discusses the problem of state fragility in Egypt and its relationship with sustainable development goals from 2006 to 2016 through utilizing data from relevant literature and reports. Qualitatively analyzing the indicators of the two main variables: fragility and sustainable development goals, the study concludes that Egypt remains politically fragile despite various relative advancements on sustainable development goals recorded. While some progress has been made on multiple socioeconomic indicators throughout the period specified, Egypt still shows an alarming level of fragility, particularly, when it comes to political aspects of democratic governance that include security, justice, rule of law, and human rights.